Một số suy nghĩ về vai trò của nhà nước trong quá trình chuyển sang nền kinh tế thị trường ở Việt Nam - Tài, Trần Anh (VNU Journal of Science: Legal Studies; Vol 20 No 2, 2004)
The article focuses on the global and local specific context affecting the process of economic reform in Vietnam. The author, therefore, points out some differences of the Vietnam Government’s role in the process of transferring from the concentrated and planning economy to the market economy.The article, moreover, generalizes the process of economic reform in Vietnam in term of the state economic reforming progress; analyzes not only the advantages and disadvantages f the policies but also its impact on achievements gained through the reform. In conclusion, the government should take more efforts to develop the market economy in Vietnam.